2015
DOI: 10.1002/crat.201500182
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric study of calcium carbonate prenucleation stage: underlining the role of CaCO3o ion pairs

Abstract: Calcium carbonate crystallization process, especially the prenucleation stage, has increasingly been the subject of several works. In the present work, a simple method based on electrical conductivity modeling applied to the FCP (Fast Controlled Precipitation) method data is used to highlight the role of CaCO 3 o ion pairs on calcium carbonate prenucleation stage. A good agreement was obtained between the resistivity vs pH curves estimated by the McCleskey model equation and obtained experimentally in a FCP te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…While calcium carbonate remains an essential model system for the further development and refinement of the PNC pathway, , it is also the system where the pivotal role of the solventwaterduring the early stages of crystallization is now crystal clear. The release of hydration water is the entropic key contribution which drives pre-nucleation ion association, beyond the ion pair, allowing for the formation of even larger PNCs . The solvent plays a key role when Mg is introduced, by inhibiting calcite growth and directly promoting aragonite nucleation in the early stages of CaCO 3 formation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While calcium carbonate remains an essential model system for the further development and refinement of the PNC pathway, , it is also the system where the pivotal role of the solventwaterduring the early stages of crystallization is now crystal clear. The release of hydration water is the entropic key contribution which drives pre-nucleation ion association, beyond the ion pair, allowing for the formation of even larger PNCs . The solvent plays a key role when Mg is introduced, by inhibiting calcite growth and directly promoting aragonite nucleation in the early stages of CaCO 3 formation .…”
Section: Discussionmentioning
confidence: 99%
“…The release of hydration water is the entropic key contribution which drives pre-nucleation ion association, 58 beyond the ion pair, 59 allowing for the formation of even larger PNCs. 60 The solvent plays a key role when Mg is introduced, by inhibiting calcite growth and directly promoting aragonite nucleation in the early stages of CaCO 3 formation. 61 The assessment of water dynamics allowed the localization of the liquid−liquid binodal limit, at which PNCs become nanodroplets of a new phase, 36 while water can control the prestructuring in the as-formed amorphous intermediates.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Among these models, it has been shown that the one proposed by McCleskey et al is the most suitable for the conductivity calculation. The methodology and basic steps of the curves modelling have been described in detail elsewhere [17].…”
Section: Conductivity Modellingmentioning
confidence: 99%
“…So, the present work focuses on the effect of chemical substances on the CaCO 3 ion pair formation and aggregation at the earlier nucleation stage. For this, our recently developed method [17] for highlighting the role of CaCO 3° ion pairs in the nucleation-growth of calcareous scale was exploited. As inhibitors, polyacrylate and polyphosphate substances were tested.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, 22 a modelling method of the resistivity vs. pH precipitation curves was developed using thermodynamic calculations of all equilibrium between various species of the CaCO 3 –CO 2 –H 2 O system. The method consisted of the comparison of four models based on equations.…”
Section: Introductionmentioning
confidence: 99%